2019
DOI: 10.1111/jgh.14562
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose aspirin can reduce colorectal cancer mortality after surgery: A 10‐year follow‐up of 13 528 colorectal cancer patients

Abstract: Background and Aim The chemopreventive effect of aspirin in colorectal cancer (CRC) is well studied, but its benefit in patients after CRC diagnosis and surgery is unclear. This study aims to investigate the effects of low‐dose aspirin use in mortality among CRC patients after surgery. Methods Patients were analyzed in two cohorts: (i) patients taking aspirin before CRC diagnosis and continued or discontinued aspirin after surgery and (ii) patients, who never used aspirin before CRC diagnosis, received or did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…For continued users (timing 4) ( 15‐17 , 29 , 33 , 41 , 47 , 50 ), there was a statistically significant association between aspirin use and improvement in both CRC-specific mortality (pooled RR = 0.76, 95% CI = 0.70 to 0.81; I 2 = 0%) and all-cause mortality (pooled RR = 0.83, 95% CI = 0.74 to 0.93; I 2 = 83.3%) ( Table 2; Supplementary Figure 4 , available online). In subgroup analysis, continued use of aspirin was associated with lower cancer-specific mortality in colon cancer patients (pooled RR = 0.66, 95% CI = 0.53 to 0.82; I 2 = 11.7%) but not rectal cancer patients (pooled RR = 0.75, 95% CI = 0.34 to 1.64; I 2 = 61.0%) ( Figure 2, A ), whereas all-cause mortality was not modified by continued aspirin use regarding separate tumor site (colon cancer RR = 0.70, 95% CI = 0.44 to 1.12; rectal cancer RR = 0.75, 95% CI = 0.54 to 1.02) ( Figure 2, B ).…”
Section: Resultsmentioning
confidence: 99%
“…For continued users (timing 4) ( 15‐17 , 29 , 33 , 41 , 47 , 50 ), there was a statistically significant association between aspirin use and improvement in both CRC-specific mortality (pooled RR = 0.76, 95% CI = 0.70 to 0.81; I 2 = 0%) and all-cause mortality (pooled RR = 0.83, 95% CI = 0.74 to 0.93; I 2 = 83.3%) ( Table 2; Supplementary Figure 4 , available online). In subgroup analysis, continued use of aspirin was associated with lower cancer-specific mortality in colon cancer patients (pooled RR = 0.66, 95% CI = 0.53 to 0.82; I 2 = 11.7%) but not rectal cancer patients (pooled RR = 0.75, 95% CI = 0.34 to 1.64; I 2 = 61.0%) ( Figure 2, A ), whereas all-cause mortality was not modified by continued aspirin use regarding separate tumor site (colon cancer RR = 0.70, 95% CI = 0.44 to 1.12; rectal cancer RR = 0.75, 95% CI = 0.54 to 1.02) ( Figure 2, B ).…”
Section: Resultsmentioning
confidence: 99%
“…In patients with bladder cancer, daily aspirin administration was associated with significantly improved survival after radical cystectomy 143 . With a combination therapy comprising aspirin and NSAIDs, after surgery, lowered the risk of early recurrence of breast cancer, and colorectal cancers as well as hepatocellular carcinoma 144–146 . Dexamethasone, a classic anti‐inflammation option and a single intraoperative dose of dexamethasone, was independently associated with improved overall survival rates in patients with pancreatic adenocarcinoma 147 .…”
Section: Potential Therapeutic Strategiesmentioning
confidence: 99%
“… Unknown Unknown increased survival in cancers Newcomb et al [ 14 ] 2017 I 326 (30%) 311 (36%) II 391 (36%) 259 (30%) III 263 (24%) 225 (26%) IV 106 (10%) 61 7 (%) Unknown 311,166 using the medications at least twice per week for more than 1 month Pre-diagnostic use 1 year before diagnosis /post-diagnostic use between baseline and the 5-year follow-up interview Unknown regular use of NSAIDs after CRC diagnosis was significantly associated with improved survival in individuals with KRAS wild-type tumors Gray et al [ 23 ] 2018 A 1683(27.0%) 597(27.8%) B 2340(37.5%) 851(39.6%) C 2218(35.5%) 702(32.7%) Low-dose (75 mg) aspirin exposure was identified from dispensing records within this database users after a lag of 6 months after their first aspirin prescription Unknown either before or after diagnosis, did not prolong survival in this population-based CRC cohort. Joseph et al [ 24 ] 2019 Unknown no less than 80 mg per day at least a month Unknown lowers risk of both CRC-related mortality and overall mortality Zell et al [ 15 ] 2009 Unknown taken aspirin regularly at least once a week the total duration of use in number of years (< 1, 1, 2, 3–4, 5–9, or 10). Unknown NSAIDs are associated with decreased mortality among female CRC patients Din et al [ 4 ] 2010 Unknown reported intake of aspirin Unknown Unknown NSAID use prior to CRC diagnosis does not influence survival of colorectal cancer Coghill et al [ 14 ] 2011 Unknown at least twice per week for 1 month first, 0–6 months; second, 6 monthse2.5 years; third, 2.5–7 years; fourth, > 7 years).…”
Section: Resultsmentioning
confidence: 99%
“…The full texts of 36 records were read. Ultimately, 18 full-text studies [4][5][6][7][11][12][13][14][15][16][17][18][19][20][21][22][23][24] were obtained and assessed according to the eligibility criteria, including 1 case-control study and 17 cohort studies, with the studies comprised of more than 74,936 patients. The detailed literature search and screening process are shown in Supplement Figure 1.…”
Section: Retrieved Studies and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation